Webtoon as an Attractive Learning Medium in Reading Comprehension for 6th Semester Students of English Education UIN Prof. K.H. Saifuddin Zuhri - Siti Usrul Khotimah; Sabrina Amelita; Nur Aolia Faozah; Reksanti Ma'rifatussa'adah (Tarling : Journal of Language Education, 2022)
This research is motivated by a situation where students' reading interest is low, so there is a need for media that can make students interested in reading and learning. Webtoon is an online comic application that is quite in demand by readers of various ages, Webtoons can also be used as learning media to increase motivation and reading comprehension. The aim of this research wants to discuss about how to use Webtoon as a medium for learning reading comprehension and whether Webtoon is in accordance with the computer-Assisted Language Learning Criteria (CALL). This study uses qualitative methods, data collected by interview techniques. The respondents in this study were 6 students from 6 TBI B who use the Webtoon application as a medium for learning reading comprehension. This research was analyzed using Chapelle theory, which has six criteria where indicate that an application can be learning media. The results of this study show that using Webtoon as a medium for learning reading comprehension is in accordance with the criteria for Computer-Assisted Language Learning (CALL), namely language learning potential, learner fit, meaning focus, authenticity, positive impact and practically. The majority of respondents gave positive comments on every aspect put forward by Chapelle. Therefore, Webtoons can be used as an interesting medium for learning reading comprehension.